ANALISIS PERBEDAAN PSAK 50 & PSAK 55 DAN SAK ETAP PADA LAPORAN KEUANGAN PT.BPR PHIDECTAMA ABEPURA (Studi Kasus: PT. BPR Phidectama Abepura) - Nelly Austin Fonataba; Paulus Allo Layuk; Cornelia D. Matani (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2021)
There is a change in financial reporting from the policy before, namely PSAK 50 and 55 and the policy after, namely SAK ETAP (Financial Accounting Standards for Entities Without Public Accountability). This study aims to identify and analyze differences in financial reporting at PT. BPR Phidectama Abepura according to the policy before and after using SAK ETAP. The analytical method used is descriptive qualitative analysis, namely analyzing the results of the study using several lists of interview questions to the President Director of PT. BPR Phidectama Abepura is related to the preparation and changes to the financial statement accounts of the balance sheet and profit and loss section of the policies before and after, and then described in accordance with the literature that has been obtained. The results of this study indicate that the preparation of the balance sheet and profit and loss at PT. BPR Phidectama Abepura in 2008 and 2010 still did not experience many changes, it can be said that the financial statements as of December 2010 had not fully implemented SAK ETAP in accordance with the circulating BI letter, therefore the account that changed was only in the income statement. In contrast to the preparation of the balance sheet and profit and loss in 2011, where the preparation of the 2011 financial statements has fully used SAK ETAP. Therefore, there are significant account changes in accordance with applicable policies and in accordance with the characteristics of the BPR.